Equity valuation of CTT, Correios de Portugal, SA. - Silva, Catarina Bento Ferreira da (2017)
The present Master Thesis aims to deliver a valuation for one of the biggest companies in Portugal: CTT Correios de Portugal, S.A. The final goal is to obtain a price-target for the shares, at the year-end of 2016. After conducting an extensive research on the best method to value the company, as well as the future perspectives over the industry and regulatory body, combining both theory and practice, the chosen method for valuing CTT was stated at the DCF Model. The sum of the parts of the businesses in which the company operates – Financial Segment (including the Postal Bank) and Other Services (Mail, Business Solutions and Express & Parcels), has computed a final enterprise value of €1,035,184,270 and yielded a share price of €7.29 for the year-end of 2016. A “BUY” recommendation was given. To complement the DCF model, a multiples valuation was conducted. Most showed that CTT would trade above its peers. Lastly, a comparison with the most recent equity note from the biggest Portuguese, state owned, bank was made. All in all, the company ‘growth prospects in the Financial Services, with the Postal Bank, and the refuting of the downing in the mail and business solution segments are the key factors that support the presented CTT Investment Case.